A green approach to recovering lithium and cobalt from spent lithium-ion batteries using dilute HCl solution mixed with H. sabdariffa flower extract as a leaching agent - Tran T.T.; Nguyen T.H.; Nguyen P.D.; Lee M.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Studies on the recovery of lithium and cobalt from spent lithium-ion batteries have attracted a lot of attention in recent years. For a sustainable battery industry, processes for the recycling of valuable metals from spent batteries have been continuously improved and developed via a “green” approach. In this work, an effective process for the recycling of lithium and cobalt from spent cell phone lithium batteries was investigated using HCl solution at low concentrations in combination with H. sabdariffa flower extract. The influence of parameters such as the concentration of the extract and HCl, pulp density, reaction temperature, and time on the percentage of leached metals was investigated. In these leaching systems, the extract, which contains organic compounds, acts as a complexing and reductive agent for dissolved metals. The optimum conditions for the leaching of these metals were 90% (v/v) of extract, 0.5 mol/L HCl, 10 g/L pulp density, 90oC, and 2.0 hours. 100% Li(I) and 91.3% Co(II) were leached under the optimum leaching conditions. Li(I) and Co(II) from the leachate were completely separated by the use of AG®50W-X4 resins and the presence of the extract in the leach solution had little effect on the recovery capacity for these metals. The metal loading capacity of the resin was determined to be 37.4 mg/g Co(II) and 1.2 mg/g Li(I). Thus, the use of plant extracts such as the flower of H. sabdariffa can be considered as a promising agent for the recovery of valuable metals from spent batteries.